Outcome of single breech term deliveries at the Federal Medical Centre, Owerri, South Eastern Nigeria: a five year review - Duke, Augustine Onyeabochukwu; Duke, Chukwunonyerem Onyeaboh; Onyegbule, Onyema Athanatius; Amajuoyi, Cornelius C.; Madu, Primus I.; Enyinnaya, Enoh B. (International Journal of Research in Medical Sciences, 2017)
Background: The best mode of delivery of breech presentation for optimum neonatal outcome has been a subject of controversy over the years. Aim of current study was to determine the pattern of distribution, incidence, mode of delivery and outcome of singleton breech presentations at term among parturients at this centre. Methods: This was a retrospective study of singleton breech term delivery at the federal medical centre, Owerri between January 1, 2007 and December 31, 2011. Singleton breech term deliveries were identified from the labor ward register and the hospital numbers extracted to retrieve the case notes from the medical records department of the hospital. Some data were collected and analysed. Results: There were a total of 9624 deliveries during the study period, out of which 328 (3.4%) were singleton breech presentation at term. Term singleton breech was commoner in multiparous 200 (61%) than in primiparous 128 (39%) women. Extended (Frank) breech was the commonest type of breech presentation (60.4%) followed by flexed (complete) breech (36.0%) and footling breech (3.6%) was the least common. Assisted vaginal breech delivery was conducted in 66.2% of cases while 27.4% were delivered by emergency caesarean section and 6.4% of cases were delivered through elective caesarean section. There were one maternal and 24 perinatal death. Twenty one (87.5%) of perinatal deaths those occurred in unbooked mothers. Conclusion: Although assisted vaginal breech delivery for singleton breech term delivery was commonly performed in our centre, elective caesarean delivery gives the better neonatal outcome for fetuses presenting breech.